2021
DOI: 10.3390/s21123974
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Laboratory and Daily-Life Gait Speed Assessment during ON and OFF States in Parkinson’s Disease

Abstract: Accurate assessment of Parkinson’s disease (PD) ON and OFF states in the usual environment is essential for tailoring optimal treatments. Wearables facilitate measurements of gait in novel and unsupervised environments; however, differences between unsupervised and in-laboratory measures have been reported in PD. We aimed to investigate whether unsupervised gait speed discriminates medication states and which supervised tests most accurately represent home performance. In-lab gait speeds from different gait ta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 48 publications
(80 reference statements)
1
12
0
Order By: Relevance
“…As there is increasing evidence that gait measured in the lab does not reflect daily-life gait [ 19 , 20 , 21 ], there is increasingly more interest in measurement systems that allow for continuous gait analysis in ambulatory settings. Therefore, the use of inertial measurement units (IMUs) is especially attractive, as these can be used to measure gait in ecologically valid environments, such as the home environment, thereby painting a more complete picture of health status [ 22 , 23 ] and providing clinical information that is complementary to standardized lab-based assessments [ 20 , 21 , 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…As there is increasing evidence that gait measured in the lab does not reflect daily-life gait [ 19 , 20 , 21 ], there is increasingly more interest in measurement systems that allow for continuous gait analysis in ambulatory settings. Therefore, the use of inertial measurement units (IMUs) is especially attractive, as these can be used to measure gait in ecologically valid environments, such as the home environment, thereby painting a more complete picture of health status [ 22 , 23 ] and providing clinical information that is complementary to standardized lab-based assessments [ 20 , 21 , 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…This value is also a good choice according to the previous research [8], in which bout length is suggested to be larger than 10s or longer for better between group difference of gait characteristics. Another research by Corrà et al [7] also generates gait speed per bout on a interval longer than 15s so as to guarantee the accuracy of further analysis. Gait characteristics in this research are derived from video data collected with 3D camera as biosensor.…”
Section: Discussionmentioning
confidence: 99%
“…They found that gait speed is distinct in different conditions and suggested to combine them together in predicting disease conditions. Corrà et al [7] studied how to use gait speed in daily life to discriminate disease ON and OFF states. They found that gait speed in daily life reflects different aspects of mobility of PD and can complement that in clinic.…”
Section: Related Workmentioning
confidence: 99%
“…Altered gait characteristics occur early in Parkinson’s disease (PD) ( Rehman et al, 2019 ) and even years prior to diagnosis ( Del Din et al, 2019 ), with the most consistent abnormalities being a slower gait, increased variability, and asymmetry ( Del Din et al, 2019 ; Rehman et al, 2019 ; Corra et al, 2021 ). These features are related to bradykinesia and improve with levodopa ( Chien et al, 2006 ; Bryant et al, 2016 ; Corra et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Altered gait characteristics occur early in Parkinson’s disease (PD) ( Rehman et al, 2019 ) and even years prior to diagnosis ( Del Din et al, 2019 ), with the most consistent abnormalities being a slower gait, increased variability, and asymmetry ( Del Din et al, 2019 ; Rehman et al, 2019 ; Corra et al, 2021 ). These features are related to bradykinesia and improve with levodopa ( Chien et al, 2006 ; Bryant et al, 2016 ; Corra et al, 2021 ). Approximately 25% of people with PD (PwP) have unstable posture at diagnosis ( Kohat et al, 2021 ), and the incidence increases with time from diagnosis ( Kohat et al, 2021 ) often with the development of freezing of gait (FOG) ( Ge et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%